Effects of acute exposure to 1000 to 4500 m on VO2max in endurance-trained subjects - Richalet, J.-P.; Mollard, P.; Woorons, X.; Letournel, M.; Cornolo, J. (13. International Hypoxia-Symposium, February, 19-22, 2003, Banff, Alberta (Kanada), 2003)
Maximal aerobic capacity (VO2max) has been shown to decrease at moderate altitude. However, the importance of this decrease, the altitude where it appears, the influence of training status and the mechanisms involved are not clearly identified. We aimed to evaluate the importance of factors responsible for VO2max reduction in trained subjects exposed to acute hypoxia. METHODS: Nine healthy male volunteers were divided into 2 groups according to their aerobic performance : group T, trained endurance athletes (n 5 5, VO2max 5 61.1 1/26.5 ml/kg/min); group C, untrained individuals (n 5 4, VO2max 5 47.21/21.8 ml/kg/min). Subjects performed incremental cycle ergometric tests under normoxic and normobaric hypoxic conditions (1000, 1500, 2500, 3500, 4500 meters). Heart rate (HR), arterial oxygen saturation (SaO2), oxygen uptake (VO2), pH and p50 (arterialized capillary blood at rest and after 2 minutes of recovery) were measured. RESULTS: Both groups showed a progressive reduction in VO2max in hypoxia (significant at 1500 m for group T and 2500 m for group C). The percent change in VO2max at 4500 m was greater for group C (222%) than for group T (213.5%) in spite of a greater reduction in SaO2 at each altitude for group T (at 4500 m, the reduction was 32.8% for group T and 24.3% for group C). HRmax decreased at and above 1000 m for group T and at 4500 m for group C. There was no difference in exercise pH and p50 between the 2 groups. CONCLUSION: Trained subjects showed a smaller reduction in VO2max in spite of a greater reduction in maximal O2 transport (greater desaturation and reduction in HRmax). We hypothesize that in trained subjects a greater peripheral O2 extraction limits the decrease in VO2max in hypoxia but induced a greater arterial desaturation through diffusion limitation.